Analysis of Platelet Counts and Leukocyte Residues at Different Storage Times in Thrombocyte Concentrate - Tania Aryadi Pramudyawardhani; Raehana Samad; Rachmawati Adiputri Muhiddin (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Thrombocyte Concentrate (TC) is one of the blood components given as therapy to patients. Ensuring the quality of TC products is essential to know if they can be transfused to patients. This study aimed to analyze platelet counts and leukocyte residues in TC products with different storage times. Cross-sectional research with a prospective cohort design was carried out at the Blood Transfusion Unit of Dr. Wahidin Sudirohusodo Hospital, Makassar, in September 2022. The study samples were ten bags of TC products produced from whole blood using the buffy coat method. The average platelet count in TC products on the 1st, 3rd, and 5th day were 50.65x109 (± 24.58); 66.24x109 (± 34.83); 47.34x109 per unit (± 37.75). Statistical tests showed no significant decrease between the 1st, 3rd, and 5th days. A meaningful decrease was obtained on the 3rd and 5th day (p < 0.05), while on the ratio of the 1st and 3rd day, there was no meaningful difference (p > 0.05). The average number of leukocytes is 0.0727x109 per unit (± 0.0659). The average number of platelets and leukocyte residues in TC products is by PERMENKES No. 91 of 2015 standards. Thrombocyte concentrate products can be used until the 5th day of storage.